STUDENT’S PERCEPTION OF TEACHER’S USE OF HUMOR IN THE CLASSROOM - Manurung, Galatia; Jamaluddin Nasution; Divia Priyanka; Kenzo (Rahis Cendekia Indonesia, 2025)
The use of humor in the classroom has been widely regarded as an effective pedagogical strategy to create a positive learning atmosphere, foster engagement, and reduce student anxiety. This study aims to explore students’ perceptions regarding their teachers’ use of humor during English language instruction. Employing a qualitative descriptive design, the researchers collected data through semi-structured questionnaires and follow-up interviews with 30 undergraduate students in the English Education Department at Universitas Rahiscendekia Indonesia. The findings indicate that most participants perceive humor as a helpful tool for enhancing comprehension and maintaining motivation. However, some students expressed concerns about humor that is perceived as inappropriate or excessive. The study highlights that the successful use of humor depends on teachers’ sensitivity to students’ backgrounds and the relevance of humorous content to instructional objectives. Implications suggest the importance of professional development programs to train educators in using humor effectively while maintaining classroom decorum. Additionally, the results reveal that humor contributes to building positive relationships between teachers and students, making instructors appear more approachable and supportive. This relational benefit was especially valued by learners who often experience anxiety in language classrooms. Future research is recommended to examine the long-term effects of humor on academic achievement and to explore its application across diverse cultural and educational contexts.